Daerah Istimewa Yogyakarta Dalam Perspektif Filosofis, Historis Dan Yuridis - Dahlan Thaib (Jurnal Hukum IUS QUIA IUSTUM, 2005)
Constitution 1945 has changed for times, however, there isno respect to the continuity of the district government which possess specific andspecial nature. Even the State recognizes and respects the Unity ofindigenous people including the living traditional rights and itis compatible with the development ofthe society and NKRI principle.